Microbial decolorization of anthraquinone dyes: batch and continuous treatment systems - a mini-review - Mohanty, Swati Sambita; Kumar, Arvind (Frontiers in Environmental Engineering, 2025)
IntroductionEnvironmental pollution and human exposure to dyes, particularly anthraquinone-based dyes from industries like textiles, paints, plastics, paper, and tanneries (a significant source of toxic waste in India), have increased. These dyes in wastewater pose a serious environmental threat due to their complex structure and resistance to traditional degradation methods. This mini-review explores microbial strategies as a cost-effective and environmentally friendly alternative for decolorizing these dyes, highlighting the limitations of physico-chemical methods.MethodsThis review examines existing literature on microbial decolorization of anthraquinone dyes. It discusses the isolation of microorganisms adapted to dye-contaminated environments as a key strategy. The factors influencing microbial decolorization in batch systems, such as optimal pH, temperature, and inoculum volume, are analyzed. Furthermore, continuous systems like packed bed bioreactors are explored, with a focus on the impact of flow rate and influent dye concentration on treatment efficiency.ResultsThe review synthesizes information on the effectiveness of various microbial strategies for anthraquinone dye decolorization in both batch and continuous systems. It highlights the potential of adapted microorganisms for efficient dye removal and discusses the influence of key operational parameters on decolorization performance in different reactor configurations.DiscussionThis mini-review emphasizes the growing importance of biological approaches for anthraquinone dye removal due to their cost-effectiveness and environmental sustainability compared to physico-chemical methods. By providing a comprehensive overview of microbial strategies, this work contributes to the development of sustainable and effective wastewater treatment solutions for dye-containing industrial effluents.